2014
DOI: 10.1080/09658211.2014.882955
|View full text |Cite|
|
Sign up to set email alerts
|

The retrieval of self-defining memories is associated with the activation of specific working selves

Abstract: This article presents two studies that investigated the impact of the retrieval of self-defining memories on individuals' sense of self. Participants recalled positive and/or negative self-defining memories, rated memory characteristics and completed measures focusing on different self-aspects. Study 1 found that participants reported higher state self-esteem after recalling a positive memory than after recalling a negative one. They also reported lower negative self-consistency and higher state self-concept c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 77 publications
2
30
0
Order By: Relevance
“…Research to date indicates that activating different 'working selves' is strongly associated with the accessibility of different memories consistent with this, such that activating positive memories may increase the accessibility of a positive working self, for example (Çili & Stopa, 2015;Conway et al, 2004). By facilitating the retrieval of negative self-constructs (Lyubomirsky et al, 1998), it is plausible to expect that abstract, ruminative thinking may increase the accessibility of illness-related memories and perpetuate the activation of the 'health-vulnerable' self.…”
Section: Discussionmentioning
confidence: 92%
“…Research to date indicates that activating different 'working selves' is strongly associated with the accessibility of different memories consistent with this, such that activating positive memories may increase the accessibility of a positive working self, for example (Çili & Stopa, 2015;Conway et al, 2004). By facilitating the retrieval of negative self-constructs (Lyubomirsky et al, 1998), it is plausible to expect that abstract, ruminative thinking may increase the accessibility of illness-related memories and perpetuate the activation of the 'health-vulnerable' self.…”
Section: Discussionmentioning
confidence: 92%
“…This is consistent with a recent study showing negative correlations between the CES and self-concept clarity (Boelen, 2017). In addition, having a negative event central to identity may reduce, or even eliminate, a self-protective down-regulation of negative affect (Ritchie et al, 2014) and pave the way for repeated rehearsal of the stressful event, which can reduce self-esteem (Çili & Stopa, 2015). However, these possibilities are largely speculations awaiting future research.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research has identified associations between the thematic content of life story memories, including redemption and contamination themes (McAdams, Reynolds, Lewis, Patten, & Bowman, ) or agency and communion themes (Adler, Harmeling, & Walder‐Biesanz, ; McAdams, Hoffman, Day & Mansfield, ), and measures of psychological functioning. Cili and Stopa () found that when people are explicitly instructed to recall either positive or negative memories, recall of positive past events led to higher state self‐esteem and state self‐concept clarity compared to recall of negative past events. However, none of these studies have compared effects of recalling chapters to effects of recalling specific memories.…”
Section: What Is a Life Story Chapter?mentioning
confidence: 99%